Efek samping glaukoma pada penggunaan antipsikotik atipikal - Oktavianus Suardiyasa, I Made Daniel; Dundu, Anita Elisabet; Kairupan, Bernabas H. R. (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: Antipsychotics are the primary therapy supported by the first scientific evidence to treat schizophrenia and other primary psychotic disorders. Aim: To determine the side effects of glaucoma in the use of atypical antipsychotics and to identify the types of atypical antipsychotic drugs that can give glaucoma side effects. Methods: This study is a literature review research, searching journal publications on Google Search, Google Scholar, PubMed, ClinicalKey using selected keywords. Articles or journals that fit the inclusion and exclusion criteria were taken for further analysis. Result: Several cases of glaucoma side effects were found in the use of atypical antipsychotics such as ziprasidone, olanzapine and aripiprazole. Conclusion: Several cases of glaucoma side effects occurred when using atypical antipsychotics such as ziprasidone, olanzapine and aripiprazole. Glaucoma cases occur in individuals who have risk factors and in eyes that have a tendency to develop glaucoma such as elderly individuals and have anatomical abnormalities in the trabecular flow. Keywords: atypical antipsychotics, glaucoma, ziprasidone, olanzapine, aripiprazole